Differences Of The Effectiveness Of Health Explanation Methods And The Use Of The Adolescent Health Kader KIE Book Toward The Knowledge Of Adolescents At Posyandu, - Mustilah, Feni; AnggrainI, AnggrainI; Putri, Ratna Dewi (Universitas Malahayati Bandar Lampung, 2024)
Background: Adolescent reproductive health is an interesting topic in various circles, especially in Indonesia. There are cases of teenage pregnancy at school age, namely 15 years and having to drop out of school, there are also teenagers who get married at the age of 16 years with a 16 year old peer partner. Lack of knowledge and education about Reproductive Health is one of the triggers for these things.The purpose of the study: To find out the difference in adolescent knowledge in Sipatuhu Village, Banding Agung District, South Oku Regency in 2021, before and after being given counseling on the lecture method and with the IEC Book of Adolescent Health Cadres.Research method: This type of research is quantitative, with a quasi-experimental method with a two-group design, pre-test and post-test. Which examines the differences in the effectiveness of health counseling with the lecture method and the use of the IEC book for adolescent health cadres on adolescent knowledge at the posyandu, Sipatuhu Dua village, South OKU district, South Sumatra in 2021. The population and sample are 50 people and use purposive sampling technique. This data was taken using a questionnaire, data analysis was univariate (mean) and bivariate (t-test).Results: The results obtained in the lecture method the average value of adolescent knowledge increased by 3,000 with a standard deviation of 1.384. Meanwhile, with the book method, the average value of adolescent knowledge increased by 3.120 with a standard deviation of 1.590. The results of statistical tests using an independent T-test in the lecture method group showed a p-value of 0.000, at a value of 0.05, p-value <0.05. In the book method group, it shows a p-value of 0.000, at a value of 0.05, p-value <0.05. So it was concluded that there was a significant difference in posttest scores between the lecture method group and the book method group. This shows that health education using the book method is more effective. Suggestions for youth, encourage them to take part in various activities and organizations such as youth posyandu, to gain more knowledge related to adolescent reproductive health.Keywords : lecture and book method counseling, adolescent knowledge, adolescent reproductive health ABSTAKLatar Beakang : Kesehatan reproduksi remaja menjadi salah satu topik yang menarik di berbagai kalangan, terutama menjadi hal penting di Indonesia. Adanya kasus kehamilan remaja pada usia sekolah yaitu 15 tahun dan harus putus sekolah, ada juga remaja yang menikah pada usia 16 tahun denagn pasangan sebaya berusia 16 tahun juga.Kurangnya pengetahuan dan pendidikan tentang Kesehatan Reproduksi menjadi salah satu pemicu terjadinya hal-hal tersebut. Tujuan penelitian : Diketahui perbedaan pengetahuan remaja Di Desa Sipatuhu Kecamatan Banding Agung Kabupaten Oku Selatan Tahun 2021,sebelum dan sesudah diberi penyuluhan metode ceramah dan dengan Buku KIE Kader kesehatan remaja.Metode penelitian : Jenis penelitian kuantitatif, dengan metode quasi experiment dengan design two group, pre test post test. Yang meneliti tentang perbedaan efektivitas penyuluhan kesehatan metode ceramah dan penggunaan buku KIE kader kesehatan remaja terhadap pengetahuan remaja di posyandu desa sipatuhu Dua kabupaten OKU Selatan SUMSEL tahun 2021. Jumlah Populasi dan sampel sebanyak 50 orang dan menggunakan teknik purposive sampling. Data ini diambil menggunakan kuisioner, analisa data secara univariat (rata-rata) dan bivariat ( t-test)Hasil : Hasil penelitian didapat pada metode ceramah nilai rata-rata pengetahuan remaja meningkat sebesar 3,000 dengan standar deviasi sebesar 1,384. Sedangkan dengan metode buku nilai rata-rata pengetahuan remaja meningkat sebesar 3,120 dengan standar deviasi sebesar 1,590. Hasil uji statistika dengan menggunakan uji T independen pada kelompok metode ceramah menunjukkan nilai p-value 0,000, pada nilai α 0,05, p-value < 0,05. Pada kelompok metode buku, menunjukkan nilai p-value 0,000, pada nilai α 0,05, p-value < 0,05. Sehingga disimpulkan bahwa ada perbedaan signifikan nilai posttest antara kelompok metode ceramah dengan kelompok metode buku. Hal ini menunjukkan penyuluhan kesehatan dengan metode buku lebih efektif. Saran bagi remaja,anjurkan remaja untuk mengikuti berbagai kegiatan dan organisasi seperti posyandu remaja, untuk mendapatkan pengetahuan lebih banyak terkait kesehatan reproduksi remaja. Kata Kunci : penyuluhan metode ceramah dan buku,Pengetahuan remaja,kesehatan reproduksi remaja